ANAK UNDERACHIEVER: ANALISIS FAKTOR-FAKTOR PENYEBABNYA - Sulaeman, Erwin; Choiriyah, Choiriyah (Journal of Early Childhood Education (JECE), 2020)
This study aims to determine the factors that cause high IQ students who experience learning difficulties so that learning outcomes are low (underachiever). This study uses a qualitative descriptive approach to the interpretive-constructivist model. The research subjects were 2 elementary school students who had high IQ but had low learning outcomes under the Minimum Completeness Standard (MCS). Data collection techniques through interviews, observation and documentation. The results showed that the factors causing the underachiever were: burdening with the characteristics of not caring about learning and the inability to do learning assignments and a family environment with caring but possessive parents 'attitudes and parents who were more concerned with learning than facilitating students' potential.